2001
DOI: 10.1177/074873040101600310
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Triacylglycerol Responses in Simulated Night and Day Shift: Gender Differences

Abstract: A number of reports suggest that shift workers have an increased risk of coronary heart disease (CHD). One contributing factor may be the consumption of meals at night with consequent altered postprandial responses. This study investigated circulating triacylglycerol (TAG), a possible risk factor for CHD, after meals during a simulated day and night shift. Twenty-five healthy participants (10 women and 15 men) were studied. They were given a pre-meal at 0800 h and a test meal at 1330 h on a simulated day shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…These factors are all considered as risk factors for body weight gain and the onset of the metabolic syndrome, type 2 diabetes, and cardiovascular diseases (19,53,56). Interestingly, Sopowoski et al (57) found that men have higher and longer elevated triacylglycerol levels compared to women in response to eating at night. These findings could mean that women have lower risk to gain weight as a result of night work compared to men.…”
Section: Explanation Of the Findingsmentioning
confidence: 99%
“…These factors are all considered as risk factors for body weight gain and the onset of the metabolic syndrome, type 2 diabetes, and cardiovascular diseases (19,53,56). Interestingly, Sopowoski et al (57) found that men have higher and longer elevated triacylglycerol levels compared to women in response to eating at night. These findings could mean that women have lower risk to gain weight as a result of night work compared to men.…”
Section: Explanation Of the Findingsmentioning
confidence: 99%
“…In the last decade, epidemiological studies have documented that postprandial TG concentrations are correlated with the incidence of cardiovascular events, suggesting that postprandial plasma TGs are a good marker for the risk of cardiovascular disease (Miller et al 2011). In humans, postprandial TG responses vary during the day, being higher during the resting phase than during the active phase (Romon et al 1997;Sopowski & Hampton, 2001), suggesting the involvement of the SCN or behavioural activity. Moreover, epidemiological studies show that night workers, who have activity and meal patterns shifted towards the night, have an increased risk for cardiovascular diseases (Gu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 5 studies included, 3 were conducted in men. Two studies included both males and females, of which one aimed to investigate sex-differences in postprandial TAG (Sopowski et al, 2001). Sample size ranged from 9 to 25; this results in a combined total of 73 participants, of which most were male ( n = 61).…”
Section: Resultsmentioning
confidence: 99%